Kajian Transformasi Visual Desain Karakter Eevee pada Game Pokémon Series Generasi I-V - Dewi Isma Aryani; Imam Santosa; Alvanov Zpalanzani (ITB Journal Publisher, LPPM ITB, 2013)
Pokémon game series is a representation of the media culture that offers a world of simulation by creating signs through storyline, gameplay, environment, as well as game characters, so that it becomes a part of digital culture. The design of Pokémon character, in this case is Eevee, is able to generate its fans curiosity and addiction resulted from the application of Manga-matrix method, color theory and morphological-forced-connections technique through the visual transformation of character design itself. This study is a qualitative research that conducted through the application of Manga-matrix principle including internal and external factors on the characters, similarity analysis or the relation among the theories connected to visual element and the interpretation of character meaning, and the combination of character design theories as the reflection of the Satoshi Tajiri as well as Japanese society’s ideology or thinking pattern in cultural implementation. The analysis shows that Eevee’s changing form still contains similarity with its existence of additional elements creates variety of forms in Eevee’s character visualization. Those Eevee’s form variety becomes the essence of the creation of the character as the media that introduces the visual transformation of character design in a game, in this matter is the Pokémon game series.